Mental health needs and implementation barriers for psychosocial support among forcibly displaced Ukrainians in Poland, Romania, and Slovakia: a qualitative analysis - Olechno, Emilia; Weinreich, Karl J.; Frankova, Iryna; Purgato, Marianna; Bartucz, Monica; Barbui, Corrado; Klymchuk, Vitalii; Čavojská, Katarína; Kucukozkan, Emrah; Maximets, Natalie; Mooren, Trudy; Patania, Federica; et al. (Frontiers in Psychiatry, 2025)
BackgroundSince the beginning of Russia’s offensive war against Ukraine, over 6.3 million forcibly displaced persons (FDPs) have settled in the European Union. This study aimed to identify key mental health and psychosocial challenges among Ukrainian forcibly displaced persons (FDPs), including symptoms of depression, anxiety and PTSD, as well as barriers to implementing mental health and psychosocial support (MHPSS) in Poland, Romania, and Slovakia.MethodUsing a two-step qualitative design, we conducted free-listing (n = 18; convenience sample recruited from partner organisations) and key informant interviews (n = 12; snowball sample) with FDPs from Ukraine. All interviews were audio-recorded, transcribed, and pseudonymised. Data was analysed using an inductive approach, allowing themes to emerge from the data itself, and was then organised deductively using the System Innovation Approach framework. Data was coded independently by two authors and synthesised using consensus discussions.ResultsFindings revealed that Ukrainian FDPs face key challenges, including uncertainty about the future, a sense of disconnection from their communities, and the profound emotional impact of losing established roles, identity, and sense of purpose tied to their former social and professional lives. Important factors to consider when implementing MHPSS include stigma and culturally appropriate ways of communicating distress, such as somatisation. Participants also emphasised the importance of framing mental health services as health promotion to encourage uptake and acceptance.ConclusionsThese findings highlight urgent, multidimensional needs for Ukrainian FDPs and contribute to developing sustainable mental health support strategies for displaced populations affected by armed conflict or forced displacement.